The study of the velocity and the accuracy in experienced kendo practioner`s attack. - Sueyashi, F.; Nishihira, Y.; Kwahara, Y.; Fukumoto, H.; Hayashi, K.; Hayashi, Y.; Koda, K. (Advances in Exercise and Sports Physiology, 2013)
In kendo, it is very important to digest the countless sensory information within an extremely short period of time before discharging the attack. So far a lot of studies conducted on kendo have been on historical researches or coaching methodologies. In addition, researches from an exercise physiological point view, such as adapting reaction task and MCV (motor nerve conduction velocity) of experienced kendo practioners, have already been reported in great detail. The findings of these studies show that perhaps the faster reaction process of brain and MCV of experienced kendo practioners are the results of years of training. However, until now, these researches used experimental task and methodologies, that are far apart from an actual situation in kendo. Only few investigations have been conducted on the accuracy of the attack or on information processing in the central nervous system from the time one is faced with an opponent to the moment of the attack. Therefore, the purpose of this study is to clarify the velocity of the attack and its accuracy. The experiment will also look at the neurological state before the attack. The subjects of the experiment will be experienced kendo practioners with 13 years(±2) of experience and regular people.